Analysis of the Decline in Export Agency Services Using the 5-Whys Method at PT Bukit Prima Bahari Palembang Branch - Miranda Pricilia Meluwu (Journal Research of Social Science, Economics, and Management, 2026)
The sharp decline in demand for mother-vessel export agency services at PT Bukit Prima Bahari (BPB) Palembang Branch in recent years highlights the need to identify its root causes. Using the 5 Whys technique, this case study analyzes data from semi-structured interviews, port-call observations, and operational documents. The findings point to two key issues: disrupted commercial continuity due to turnover of key personnel, and weak value framing that made BPB’s pricing appear high without explicit service evidence. The study recommends strengthening the value proposition, standardizing “apple-to-apple” price comparisons, and improving commercial governance to enhance document readiness and coordination. These insights support more effective service recovery, price realization, and operational reliability.